2020
DOI: 10.1038/s41598-020-71697-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar transport, spin polarization and thermoelectricity in complex silicene structures

Abstract: 2D materials open the possibility to study Dirac electrons in complex self-similar geometries. The two-dimensional nature of materials like graphene, silicene, phosphorene and transition-metal dichalcogenides allow the nanostructuration of complex geometries through metallic electrodes, interacting substrates, strain, etc. So far, the only 2D material that presents physical properties that directly reflect the characteristics of the complex geometries is monolayer graphene. In the present work, we show that si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…In the case of conductance, it shows an oscillatory behaviour that can be directly described by bound states [33]. Similarly, self-similar patterns in silicene were studied, and it was reported that scaling rules in conductance and thermoelectric effects between generations of silicene structures [34].…”
Section: Introductionmentioning
confidence: 91%
“…In the case of conductance, it shows an oscillatory behaviour that can be directly described by bound states [33]. Similarly, self-similar patterns in silicene were studied, and it was reported that scaling rules in conductance and thermoelectric effects between generations of silicene structures [34].…”
Section: Introductionmentioning
confidence: 91%
“…According to several studies, environmentally wasted heat represents more than 50% of the energy produced 27 . Numerous theoretical studies have been carried out on the thermoelectric effect in various systems based on 2D materials, showing an improvement in the thermoelectric performance 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic makes silicene useful in the spintronic applications and semiconductor industry, such as room temperature field-effect transistor (FET) [5]. In recent years, many studies have been focused on the transport properties in silicene structures [6][7][8][9][10][11][12][13][14]. Kharadi et al [11] demonstrated that due to the generation of band gap in silicene via hydrogenation of silicene, the spin-filtering efficiency reaches up to 96%.…”
mentioning
confidence: 99%